The possible morphological evolution of arteriovenous malformations of the brain - Cabieses, Fernando (1956)
The purpose of this communication is to present a hypothesis about the possible sequence in the development of these lesions from simple arteriovenous communications congenital. The basic principles of this theory have been expressed in general terms in other opportunities. Now we will just present a series of angiographic studies in many patients to give an idea of the various stages through which can pass through an injury of this nature. It is known that arteriovenous communications artificially produced in other organs evolve with some variations in the sequence similar to that proposed here.